Decentralization and Rice Production in Bali Province - Vavorita, Barlianti (FIA UB, 2018)
This study want to explore the link between decentralization and rice production. Also Analyses the effectiveness of local government policy in controlling rice production. To examine this aim, it need to determine the factor influencing rice production in Indonesia which is then used to analyze the linkage with decentralization in Bali Province. In order to determine the significant factor influencing rice production, Linear Regression Analysis is used. This study tried to answer two research question, which are (1) What is the significant determinant factor that influencing rice production in Indonesia. and (2) How is the relationship between decentralization and rice production in Bali Province. This study used secondary data analysis. Data collected from Indonesia Statistic Agency, FAO, Worldbank and other necessary document. The result of this test shows that the R square is 0.995.Â It means that the determinant factors are significantly influence the rice production in Indonesia, especially for rice area and fertilizer used. The agricultural employment is not significantly influence the rice production. Local government need to be more aware and sensitive of their people need, otherwise the people need to be more active through participation community.